Milk fat globule size, phospholipid contents and composition of milk from purebred and Alpine-crossbred Mid-Eastern goats under confinement or grazing condition. (July 2016) - Argov-Argaman, Nurit; Hadaya, Oren; Glasser, Tzach; Muklada, Hussein; Dvash, Levana; Mesilati-Stahy, Ronit; Landau, Serge Yan
Abstract: Milk fat globule (MFG) size and phospholipids (PL) content and composition were determined in milk collected at 65 (pretreatment), 110, 135 and 170 days of lactation from goats randomly assigned to grazing in Mediterranean brushland or fed clover hay indoors, in addition to concentrate. Daily feed intake and dietary contents of neutral detergent fibre and acid detergent fibre were higher in grazing goats, associated with milk richer in fat, with larger MFGs and 20% higher PL content. Smaller MFGs, produced by all confinement groups, was associated with 15 μg g −1 fat higher milk PL content. The greatest effect was found in the Damascus goats, with over 44% higher PL concentration, on milk fat basis, in the confined compared with grazing group. Our understanding of how PL content is modulated by the interaction between genetic background and nutrition will enable to achieve either PL-rich milk or PL-enriched milk fat.